Color appearance of small stimuli presented in central and near peripheral visual fields. Issue 4 (12th January 2021) - Mogi, Shuichi; Sakurai, Masato; Ishikawa, Tomoharu; Ayama, Miyoshi
Abstract: This study investigates the change in the color appearance of a small stimulus with a diameter of 0.5° presented at various locations along the vertical and horizontal meridians in the visual field. To determine the color appearance, the hue and saturation judgment method and the categorical color naming method were used. The results obtained using these two methods at 0° exhibit the same quality of color appearance as that of a stimulus with a diameter of about 2° reported in previous studies. A more rapid decrease in perceived saturation and hue shift toward yellow in reddish and greenish stimuli are indicated in the hue and saturation judgment, whereas early distinction of "red" and persistence of "yellow" and "blue" responses are observed in the categorical color naming method. Despite the evident change in color appearance for each stimulus, the relationship between the responses obtained by the two methods for all stimuli was approximately the same across the visual field examined here. The unique hue component needed to elicit the color name of "yellow, " "green, " or "blue" is nearly constant along the eccentricity. However, the hue component of "red" is significantly higher than that of the other primary colors, especially at 0°, which suggests the specificity of that color.